Proceedings of SPE Middle East Oil and Gas Show and Conference 2007
DOI: 10.2523/105025-ms
|View full text |Cite
|
Sign up to set email alerts
|

Constant-Pressure Analysis of Infinite-Conductivity Fractured Gas Wells Influenced by Non-Darcy Flow Effects

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractNon-Darcy flow effects have long been recognized to have serious adverse impact on the performance of high-flow rate gas wells. These effects may mask the presence of fractures around the wellbore of naturally fractured reservoirs and may render the effective fracture conductivity and fracture halflength of hydraulically fractured wells much less than the designed parameters. Proper diagnosis of the post-fracture well test and good estimation of the fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Several studies have been done on turbulence effects in hydraulically fractured gas wells (Wang and Economides, 2004;Gil et al, 2001;Lolon et al, 2004;Kakar et al, 2004;Miskimins et al, 2005;Ouyang, 2007;Huang and Ayoub, 2007;Friedel et al, 2007;Nashawi, 2007) and gas condensate wells Indriati et al, 2002;Ravari and Ibrahim, 2005;Ravari et al, 2007;Mahdiyar et al, 2008). Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well.…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 96%
“…Several studies have been done on turbulence effects in hydraulically fractured gas wells (Wang and Economides, 2004;Gil et al, 2001;Lolon et al, 2004;Kakar et al, 2004;Miskimins et al, 2005;Ouyang, 2007;Huang and Ayoub, 2007;Friedel et al, 2007;Nashawi, 2007) and gas condensate wells Indriati et al, 2002;Ravari and Ibrahim, 2005;Ravari et al, 2007;Mahdiyar et al, 2008). Studies (Gil et al, 2001;Ubani and Evans, 1982) showed that significant turbulence flow can exist in a fracture at any time in the life of a vertically fractured gas well.…”
Section: Turbulence In Hydraulically Fractured Vertical Gas Wellmentioning
confidence: 96%